How do you solve y = -5x + 30 and y = 6 - 2x?

1 Answer
Mar 23, 2016

Since both of the equations tell you what y is, we know that the solution to the system of equations must satisfy both equations.
So the y value from the first equation must be equal to the y value for the second equation.


And. #24=3x#
So X = 8

Now that you have the X value you can substitute into either the first or the second equation to get the y value.
Hint, pick the simpler equation, that is the one with the smaller coefficients, so as to not over exert yourself.